Propagation and Characterization of Influenza Virus Stocks That Lack High Levels of Defective Viral Genomes and Hemagglutinin Mutations - Xue, Jia; Chambers, Benjamin S.; Hensley, Scott E.; López, Carolina B. (Frontiers in Microbiology, 2016)
Influenza virus infections are responsible for more than 250,000 deaths annually. Influenza virus isolation, propagation, and characterization protocols are critical for completing reproducible basic research studies and for generating vaccine seed stocks. Detailed protocols for the isolation and identification of influenza virus have been recently reported (Eisfeld et al., 2014). However, there are few standardized protocols focused on the propagation and characterization of viral isolates, and as a result, viruses propagated in different conditions in different laboratories often have distinct in vitro and in vivo characteristics. Here, we focus on influenza A virus propagation and characterization in the laboratory taking into consideration the overall quality and composition of the virus stock to achieve consistency in virus yield, virulence, and immunostimulatory activity.